The Prophet’s (PBUH) Treatment of Non-Muslims: In the Context of Interfaith Harmony - Tanzeela D/O Muhammad Arif; Associate Professor Dr. Naseem Akhter (Corresponding Author) (Journal of Religion and Society, 2025)
The study paper examines the non-Muslim treatment of Prophet Muhammad (PBUH) in regard to interfaith peace by showing how his excellent behavior is an everlasting example of coexistence. The paper notes that the method of the Prophet was based on compassion, justice, and respect despite the strong contention and religious divergence. Based on the Quran, Hadith, and the Prophetic biography (Seerah), it shows how the Prophet (PBUH) encouraged interfaith dialogue and social justice with the help of treaties, ethical conduct and inclusiveness in governance. Some of these liquidating factors include the Mithaq-e-Madina (the Charter of Medina) that granted Jews and other communities, religious, and civil rights and Sulh Hudaybiyyah or a peace treaty between the Prophet and Quraysh, which displays his diplomacy and ability to take the long-term vision on peace. Religious tolerance is as illustrated by his humane treatment of delegations such as the Christians of Najran, among whom he gave them the license to worship at the Prophet?s Mosque. The personal experiences, e.g. when he visited a Jewish boy that was sick, when he forgave people in Ta if, though they were not friendly, and when he transformed the character of Thumamah bin Uthal, demonstrate how the Prophet managed to appeal to the heart by means of mercy. The given work underlines that the attitude of the Prophet toward non-Muslims was not limited to the political need but was based on his mission as a prophet of mercy to the whole world. His ethical and respectful relation with others was the base of the multi-faith society in Medina. The study finds that the model of interfaith coexistence developed by the Prophet (PBUH) is not only historically important but also a timely mode of tackling the contemporary religious and cultural conflicts. His biography serves as the best example that justice, respect, and peace are the pillars of Islamic relations with non-Muslims. Keywords: Interfaith Harmony, Prophet Muhammad (PBUH), Charter of Medina, Religious Tolerance, Non-Muslims in Islam, Sulh Hudaybiyyah, Peaceful Coexistence